Super-reflector enabled by non-interleaved spin-momentum-multiplexed metasurface - Xu, He-Xiu (2023)
Electromagnetic wave multiplexing, especially for that occurring at different incidences (spatial-frequency multiplexing), is pivotal for ultrathin multifunctional interfaces and high-capacity information processing and communication. It is yet extremely challenging based on passive and compact wave elements, since the wave excitation and scattering channels are exclusively coupled through gradient phases and hence momentum matching condition at the interface. Here, we propose a spin-momentum multiplexed paradigm called a super-reflector enabling on-demand control of both retroreflections and anomalous reflections using a non-interleaved single-celled metasurface. By multiplexing four channels connecting two spin states excited onto each input of three spatial frequencies, a total of twelve channels are engineered, among which three are retroreflected channels and the residual are anomalous reflection ones. Our compound multiplexed super-reflector allows five degrees of freedom in circular polarization Jones' matrix, approaching the intrinsic upper limit of such planar metasurface. The concept has been experimentally verified by a proof-of-concept super-reflector at microwave frequency, showcasing twelve reflected beams and a high efficiency exceeding 90.6% defined as the ratio of reflected power to incidence for each channel beam. Our strategy opens a new avenue for angle multiplexing and angle-resolved metadevices toward the capacity limit of 2D planar Jones' matrix.